Apoptotic cell-derived extracellular vesicles: structure–function relationships. (5th April 2019) - Grant, Lois R.; Milic, Ivana; Devitt, Andrew
Abstract : Apoptosis is an essential process for normal physiology and plays a key role in the resolution of inflammation. Clearance of apoptotic cells (ACs) involves complex signalling between phagocytic cells, ACs, and the extracellular vesicles (EVs) they produce. Here, we discuss apoptotic cell-derived extracellular vesicles (ACdEVs) and how their structure relates to their function in AC clearance and the control of inflammation, focussing on the ACdEV proteome. We review the current knowledge, ongoing work and future directions for research in this field.